Investigating the economic and financial damage around currency peg failures - Colin Ellis; Emilia Gyoerk (Journal of Risk and Financial Management, 2019)
The choice and structure of a country's exchange rate regime has wide implications for the effectiveness and flexibility of monetary policy tools, as well as for economic and financial stability. We examine 21 instances where exchange rate pegs have been abandoned in the past, to gauge the potential economic damage associated with pegs failing. The sample includes major exchange rate shifts over the past thirty years, spanning from the Latin America currency crises of the 1990s to the peg abandonment in Egypt in 2016. Given the close interconnection of banks to the sovereign and the real economy, risks often flow through to, and can also be magnified by, the banking system. We therefore examine the interaction of currency peg abandonment with the occurrence of a banking crisis to investigate the different circumstances and impacts of exchange rate pegs failing. We have found that countries that simultaneously suffered a systemic banking crisis during the period of exchange rate regime shift also experienced significantly greater economic and financial damage following the adoption of a freely floating exchange rate. Nevertheless, regardless of whether there was a banking crisis, countries start showing signs of recovery after the same amount of time once the currency floated.
Keywords: 330; exchange rates; currency pegs; banking crises